MEMBANGUN IKATAN SOSIAL DAN KEPEMIMPINAN PARTISIPATIF MELALUI LITERASI KOMUNIKASI DI TINGKAT RUKUN TETANGGA - Yugih Setyanto (Jurnal Serina Abdimas, 2026)
This community service activity was conducted in RT 4/RW 4, Sukabumi Utara Sub-district, West Jakarta, with the aim of increasing residents’ and Rukun Tetangga (RT) administrators’ understanding of the importance of good communication in strengthening social bonds and enhancing local leadership effectiveness. In the context of a dynamic and densely populated urban environment, effective communication serves as a fundamental foundation for building harmonious relationships, resolving conflicts, and achieving shared goals. As the key figure at the most basic level of the social structure, the RT leader plays a strategic role in bridging residents’ needs with broader policies and in maintaining social order and harmony. Through an interactive face-to-face approach, this activity introduces four essential aspects of effective communication: openness and honesty, empathy and understanding, accurate information processing, and active listening skills. These four aspects have been shown to support increased trust, solidarity, and resident participation.  An analysis of the activity indicates that urban communication challenges include high population density, diverse social backgrounds, limited interaction time, and a growing reliance on digital communication. The activity underscores the importance of communication literacy as a basic skill for RT leaders to perform their social functions effectively. Investing in enhancing the communication competencies of grassroots leaders is a strategic step toward strengthening participatory leadership, fostering a harmonious environment, and building social resilience at the community level.  This activity also provides space for residents to share their experiences with communication in their neighborhoods. The interactive approach helps participants understand how to apply the concepts in practice. The results show increased awareness among residents of the importance of communication literacy in everyday life. ABSTRAK Kegiatan pengabdian masyarakat ini dilaksanakan di RT 4/RW 4, Kelurahan Sukabumi Utara, Jakarta Barat, dengan tujuan meningkatkan pemahaman warga dan pengurus Rukun Tetangga mengenai pentingnya komunikasi yang baik dalam memperkuat ikatan sosial serta efektivitas kepemimpinan lokal. Dalam konteks lingkungan perkotaan yang dinamis dan padat, komunikasi yang efektif menjadi fondasi penting untuk membangun hubungan harmonis, menyelesaikan konflik, dan mencapai tujuan bersama. Pemimpin RT, sebagai figur kunci di tingkat paling bawah dalam struktur sosial, memiliki peran strategis dalam menjembatani kebutuhan warga dengan kebijakan yang lebih luas serta menjaga ketertiban dan keharmonisan sosial. Melalui pendekatan tatap muka interaktif, kegiatan ini memperkenalkan empat aspek utama komunikasi efektif, yaitu keterbukaan dan kejujuran, empati dan pengertian, pemahaman informasi yang diterima, serta kemampuan mendengarkan aktif. Keempat aspek ini terbukti mendukung peningkatan kepercayaan, solidaritas, dan partisipasi warga. Analisis kegiatan menunjukkan bahwa tantangan komunikasi di wilayah perkotaan mencakup kepadatan penduduk, keragaman latar belakang sosial, keterbatasan waktu interaksi, serta semakin bergantung pada komunikasi digital. Kegiatan ini menegaskan pentingnya literasi komunikasi sebagai keterampilan dasar bagi pemimpin RT untuk menjalankan fungsi sosial secara efektif. Investasi pada peningkatan kompetensi komunikasi pemimpin akar rumput merupakan langkah strategis dalam memperkuat kepemimpinan partisipatif, membangun lingkungan yang harmonis, dan menciptakan ketahanan sosial di tingkat komunitas. Kegiatan ini juga memberikan ruang dialog bagi warga untuk berbagi pengalaman komunikasi di lingkungannya. Pendekatan interaktif membantu peserta memahami penerapan konsep secara praktis. Hasil kegiatan menunjukkan peningkatan kesadaran warga terhadap pentingnya literasi komunikasi dalam kehidupan sehari-hari.